Sensitivity of the residual topography to single crystal plasticity parameters in Berkovich nanoindentation on FCC nickel. (February 2016) - Renner, E.; Gaillard, Y.; Richard, F.; Amiot, F.; Delobelle, P.
Abstract: Fundamental deformation mechanisms of FCC materials under indentation have been probed at the grain scale. Experimental tests have been conducted on large-grained annealed and cold-worked polycrystalline nickel samples with a Berkovich indenter. Indentation axes have been chosen to be close to the three main crystallographic directions [001], [101] and [111]. Pile-ups and slip traces have been revealed around the residual imprints by analysing topographic measurements obtained by atomic force microscopy. It is shown that the indenter orientation in each indentation plane drives pile-ups and slip traces which in turn contain precious information about the crystallographic orientation and the hardening state of the studied grain. Imprint topographies after pile-up formation therefore carry information that one can exploit to assess some intrinsic material properties at the grain scale. A 3D finite element modelling of the nanoindentation test at the grain scale has been developed, making use of crystal plasticity constitutive laws. Six different virtual materials having the same macroscopic behaviour have been built. The simulation results show a good agreement with experimental tests and also a great pile-up sensitivity to interaction matrix components. These results pave the way to the interaction matrix identification using an inverse finite element method. Highlights: AFM topographies and dislocation slip traces are analysed after Berkovich nanoindentation at grain scale. Pile-up distribution is strongly related to the crystallographic orientation and pile-up heights to the hardening modulus. Numerical topographies in the size independent framework are in a fairly good agreement with the experimental observations. Residual topography is very sensitive to the interaction matrix components of the single crystal plasticity model.